2022
DOI: 10.3322/caac.21765
|View full text |Cite
|
Sign up to set email alerts
|

Cancer epigenetics in clinical practice

Abstract: Cancer development is driven by the accumulation of alterations affecting the structure and function of the genome. Whereas genetic changes disrupt the DNA sequence, epigenetic alterations contribute to the acquisition of hallmark tumor capabilities by regulating gene expression programs that promote tumorigenesis. Shifts in DNA methylation and histone mark patterns, the two main epigenetic modifications, orchestrate tumor progression and metastasis. These cancer-specific events have been exploited as useful t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(53 citation statements)
references
References 324 publications
1
51
0
1
Order By: Relevance
“…Extensive preclinical studies with drugs targeting the epigenetic proteins, including writers (DNA methyltransferase DNMTs, histone methyltransferase HMTs), readers (bromodomain and extraterminal BETs) and erasers (histone deacetylase HDACs), are being explored in pursuit of tumor inhibition. To date, FDA has approved seven agents -DNMT inhibitors (Azacitidine, Decitabine), EZH2 inhibitor (Tazemetostat), HDAC inhibitors (Vorinostat, Romidepsin, Belinostat, and Panobinostat) -for the treatment of diverse malignancies [20][21][22], several of which exhibited attractive antitumor effects in combination with CDK4/6 inhibitors [23][24][25]. For instance, FK228, an epigenetic eraser inhibitor (histone deacetylase inhibitor; HDACi) exhibiting anti-tumor effects against several types of solid tumors, has been shown to restrict cell proliferation and induce apoptosis in GC cells and suppress tumor growth in GC mouse models [26].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive preclinical studies with drugs targeting the epigenetic proteins, including writers (DNA methyltransferase DNMTs, histone methyltransferase HMTs), readers (bromodomain and extraterminal BETs) and erasers (histone deacetylase HDACs), are being explored in pursuit of tumor inhibition. To date, FDA has approved seven agents -DNMT inhibitors (Azacitidine, Decitabine), EZH2 inhibitor (Tazemetostat), HDAC inhibitors (Vorinostat, Romidepsin, Belinostat, and Panobinostat) -for the treatment of diverse malignancies [20][21][22], several of which exhibited attractive antitumor effects in combination with CDK4/6 inhibitors [23][24][25]. For instance, FK228, an epigenetic eraser inhibitor (histone deacetylase inhibitor; HDACi) exhibiting anti-tumor effects against several types of solid tumors, has been shown to restrict cell proliferation and induce apoptosis in GC cells and suppress tumor growth in GC mouse models [26].…”
Section: Introductionmentioning
confidence: 99%
“…Promoter methylation regulates gene expression in different cancers ( 29 , 30 ). Methylation analysis showed that promoter methylation negatively correlated with GSDMB expression level in KIRC (p < 0.001), uterine corpus endometrial carcinoma (UCEC) (p < 0.01), lung adenocarcinoma (LUAD) (p < 0.001), and pancreatic adenocarcinoma (PAAD) (p < 0.001) ( Figures 2A–D ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a study at the human genetic level found that ulcer-healing genes such as TFF2, PPARG, and RUNX3 can effectively recover from mucosal damage by coordinating methylation [38]. Folate is an essential substrate for the synthesis and maintenance of DNA methylation [39,40], which further strengthens the link between FA folate supplementation and GU.…”
Section: Discussionmentioning
confidence: 99%